2016
DOI: 10.1371/journal.pone.0168746
|View full text |Cite
|
Sign up to set email alerts
|

Schroth Physiotherapeutic Scoliosis-Specific Exercises Added to the Standard of Care Lead to Better Cobb Angle Outcomes in Adolescents with Idiopathic Scoliosis – an Assessor and Statistician Blinded Randomized Controlled Trial

Abstract: BackgroundThe North American non-surgical standard of care for adolescent idiopathic scoliosis (AIS) includes observation and bracing, but not exercises. Schroth physiotherapeutic scoliosis-specific exercises (PSSE) showed promise in several studies of suboptimal methodology. The Scoliosis Research Society calls for rigorous studies supporting the role of exercises before including it as a treatment recommendation for scoliosis.ObjectivesTo determine the effect of a six-month Schroth PSSE intervention added to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
162
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(182 citation statements)
references
References 45 publications
(60 reference statements)
5
162
0
11
Order By: Relevance
“…It is, therefore, logical to combine the internal brace with scoliosis specific exercises. Schreiber et al in a randomized controlled study on nonoperative management of AIS reported that a combination of standard of care of AIS including bracing with Schroth scoliosis specific exercises gave a better curve correction than care without exercises [8]. Our novel concept and method also combine a brace, although internal, and exercises in the management protocol.…”
Section: Discussionmentioning
confidence: 92%
“…It is, therefore, logical to combine the internal brace with scoliosis specific exercises. Schreiber et al in a randomized controlled study on nonoperative management of AIS reported that a combination of standard of care of AIS including bracing with Schroth scoliosis specific exercises gave a better curve correction than care without exercises [8]. Our novel concept and method also combine a brace, although internal, and exercises in the management protocol.…”
Section: Discussionmentioning
confidence: 92%
“…[27][28][29][30][31][32][33][34][35] AIS symptoms are frequently associated with tumors, inflammation or visceral dysfunction; this would exclude solely conservative management. The studies encompassed by this review did not include that type of patients and, after the intervention, they showed a reduction in symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…All included studies had corrective, therapeutic exercise as the independent outcome measure; 4 referred to it as Schroth exercises, [27][28][29][30] and the other 5 used different terms that covered therapeutic exercise based on self-correction and spinal stabilization. [31][32][33][34][35] The intervention period varied greatly: 3 studies included an intervention that lasted 8-12 weeks, 30,32,35 while 4 conducted interventions for 6 months, 27-29-33 and 2, for 1 year.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Obviously, general exercises or sport activities also reduce the incidence of progression in small curvatures [28] or in patients with a low risk for progression [29]. However, there is only one relevant randomised controlled trial (RCT) with an untreated control group [5], whilst other RCTs involving PSE have major flaws (amongst other things not providing an uncontrolled control group) and therefore would not contribute to high quality evidence [30,31].…”
Section: Introductionmentioning
confidence: 99%